1976
DOI: 10.1099/00221287-95-2-348
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Glycogen in Morphogenesis of Coprinus cinereus

Abstract: S U M M A R YThe quantity of glycogen that could be extracted from cultured dikaryotic mycelia of Coprinus cinereus increased during the first 5 days of growth but subsequently declined, The decline coincided with the main phase of removal of carbohydrate from the culture medium, with a major reduction in the level of soluble reducing sugars of the mycelium, and with the appearance of mature sclerotia. This result complements earlier electron microscope observations that intracellular accumulations of glycogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…During the fruiting bodies or sclerotia formation, glycogen is transported from mycelium to newly-formed structures. It is broken down into glucose, and depleted along the maturation (25,26). Beta-glucan is reserved in aging multicellular structures, such as fruiting bodies and sclerotia (5,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…During the fruiting bodies or sclerotia formation, glycogen is transported from mycelium to newly-formed structures. It is broken down into glucose, and depleted along the maturation (25,26). Beta-glucan is reserved in aging multicellular structures, such as fruiting bodies and sclerotia (5,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Development of sclerotia and often also chlamydospores correlates with the abundant occurrence of thick-walled inflated hyphal segments in the mycelial matting of older monokaryotic and dikaryotic cultures (262,294), and all these differentiations are believed to be related (262,507,510). Glycogen accumulates within the inflated hyphal cells and, if not relocated to the fruiting body (292,294), the polysaccharides seem to be transported to the sclerotia to build up the glycogen storage found in their internal inflated hyphae (190,338,342,510). Sclerotia of C. cinereus will germinate to give rise to a vegetative mycelium and do not serve in initiation of fruiting-body formation as in other basidiomycetes (335,338).…”
Section: Other Multicellular Structures: Sclerotia Mycelial Cords Pmentioning
confidence: 99%
“…Sclerotia, like chlamydospores, are also dormancy structures produced by many fungi. Studies showed that genes linked to secondary metabolite production also control sclerotia production ( Jirjis and Moore, 1976 ; Willetts and Bullock, 1992 ; Kües, 2000 ; Georgiou et al, 2006 ; Bayram and Braus, 2012 ; Calvo and Cary, 2015 ; Song, 2018 ; Shu et al, 2019 ). For example, different members of the velvet protein family interact with each other and the non-velvet protein LaeA .…”
Section: Discussionmentioning
confidence: 99%
“…Starch and sucrose metabolic pathways were mainly related to anabolism and catabolism of glycogen. In Coprinopsis cinerea , glycogen served as a carbon storage molecule, and was actively transformed between monomeric and polymeric forms during morphogenesis ( Jirjis and Moore, 1976 ). The gene encoding glucan endo-1,3-beta-D-glucosidase is relevant to the process of glycogen decomposition, which transforms Udp-glucose into D-glucose.…”
Section: Discussionmentioning
confidence: 99%